1999
DOI: 10.1074/jbc.274.32.22679
|View full text |Cite
|
Sign up to set email alerts
|

Egr-1 Mediates Extracellular Matrix-driven Transcription of Membrane Type 1 Matrix Metalloproteinase in Endothelium

Abstract: Matrix metalloproteinase activity is instrumental in processes of cellular invasion. The interstitial invasion of endothelial cells during angiogenesis is accompanied by up-regulation of several matrix metalloproteinases, including membrane type 1 matrix metalloproteinase (MT1-MMP). In this study, we show that endothelial cells stimulated to undergo angiogenesis by a three-dimensional extracellular matrix environment increase production of the transcription factor Egr-1. Increased binding of Egr-1 to the MT1-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 34 publications
3
139
0
Order By: Relevance
“…It has been reported that mechanical injury induces the activation of ERK, which transmits signals from the cytosol to the nucleus. Potential nucleus targets of ERK include the transcription factors ELK-1, Egr-1 and c-Fos, which are known to regulate cellular growth, differentiation, and migration [35][36][37][38]. Here we found that treatment of SMCs with berberine reduced the levels of phosphorylated ERK stimulated by injury, in the same concentration range that inhibited DNA synthesis and regrowth.…”
Section: Discussionmentioning
confidence: 60%
“…It has been reported that mechanical injury induces the activation of ERK, which transmits signals from the cytosol to the nucleus. Potential nucleus targets of ERK include the transcription factors ELK-1, Egr-1 and c-Fos, which are known to regulate cellular growth, differentiation, and migration [35][36][37][38]. Here we found that treatment of SMCs with berberine reduced the levels of phosphorylated ERK stimulated by injury, in the same concentration range that inhibited DNA synthesis and regrowth.…”
Section: Discussionmentioning
confidence: 60%
“…The activity of MMP-2 and MMP-9 of mouse lung fibroblast cells changed in an Egr-1-dependent manner when treated with cytomix. Although there are no Egr-1-binding sites reported in either MMP-2 or MMP-9 promoters, studies showed that the activation of pro-MMP-2 is well correlated with the expression of MIT-MMP (31), whose promoter has a binding site for Egr-1 (35). Our data suggest that EGR1 may serve as a potentially important molecule, which could play a key role in development of cigarette smoke-related COPD by regulating MMP activity and then affect the turnover of ECM proteins during pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Egr-1, a zinc finger transcription factor, has been termed an immediate-early response protein (33,34) and is potentially activated by a variety of cellular stressors. As a major transcription factor it alters gene expression of EGR1 target genes, including repair enzyme systems, angiogenic factors, cytokines (TNF-␣), apoptotic factors (Fas), cell cycle factors (p21, p53), metabolic factors, proteases (MT1-MMP) (35), and HO-1 (36).…”
Section: Discussionmentioning
confidence: 99%
“…The promoter region of MT1-MMP has many putative transcription factor binding sites (30), several of which have been demonstrated to regulate MT1-MMP expression (31-34). Among those, EGR1 was shown to play a role in induction of MT1-MMP in murine endothelial cells in collagen culture (31). In addition to EGR1, several related transcription factors including EGR2, -3, and -4, and SP1 share a similar consensus sequence (35)(36)(37)(38).…”
Section: Mt1-mmp Induction In Three-dimensional Collagen I Is Transcrmentioning
confidence: 99%